2022
DOI: 10.1186/s12887-022-03758-5
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of intrapartum group B streptococcus prophylaxis on atopic dermatitis in 2-year-old children

Abstract: Objective To understand the occurrence of atopic dermatitis (AD) in children aged 2 years on exposure to maternal group B streptococcus (GBS) antibiotic prophylaxis (IAP). Design Retrospective cohort study of 2909 mother–child pairs. Setting Taixing People’s Hospital in Eastern China. Participants Term infants born 2018–2019, followed longitudinally from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Thirteen studies failed to meet the eligibility criteria. Finally, 18 studies were included in the review (12)(13)(14)(15)(16)(17)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) (Figure 1). The inter-reviewer reliability for the selection of studies was high (κ = 0.9).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen studies failed to meet the eligibility criteria. Finally, 18 studies were included in the review (12)(13)(14)(15)(16)(17)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) (Figure 1). The inter-reviewer reliability for the selection of studies was high (κ = 0.9).…”
Section: Resultsmentioning
confidence: 99%
“…These results must be considered in light of changed guidelines that recommend the use of antibiotics before skin incision in caesarean sections ( 15 ). However, studies also suggest that the mode of delivery is an important confounder and the correlation between intrapartum antibiotic treatment and AD is increased for vaginally delivered infants but not for infancts, delivered by cesarean sections ( 12 ). Similarly, while Mubanga et al ( 24 ) have shown a modest increase in the risk of AD that was associated with maternal antibiotics in all three trimesters, Geng et al ( 23 ) have shown that the timing of antibiotic exposure is confounded by the type of antibiotic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations